2016
DOI: 10.1002/admi.201500779
|View full text |Cite
|
Sign up to set email alerts
|

Interface‐Induced Polarization in SrTiO3‐LaCrO3 Superlattices

Abstract: Epitaxial interfaces and superlattices comprised of polar and non‐polar perovskite oxides have generated considerable interest because they possess a range of desirable properties for functional devices. In this work, emergent polarization in superlattices of SrTiO3 (STO) and LaCrO3 (LCO) is demonstrated. By controlling the interfaces between polar LCO and non‐polar STO, polarization is induced throughout the STO layers of the superlattice. Using X‐ray absorption near‐edge spectroscopy and aberration‐corrected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
6
20
0
Order By: Relevance
“…This enabled the extraction of the band alignment across the entire 15-unit-cell structure through careful modeling of the core-level peak positions as a function of incoming angle, producing good agreement with DFT models [136,137].…”
Section: Standing-wave Xpsmentioning
confidence: 93%
“…This enabled the extraction of the band alignment across the entire 15-unit-cell structure through careful modeling of the core-level peak positions as a function of incoming angle, producing good agreement with DFT models [136,137].…”
Section: Standing-wave Xpsmentioning
confidence: 93%
“…For instance, elastic strain engineering is one of the most interesting approaches to tune physical properties . Other approaches to manipulate the functional properties of thin films include chemical doping, interface engineering, octahedral rotation, epitaxial stabilization, polarization doping, and dimensional confinement . By carefully selecting substrates and/or buffer layers, different strain states can be achieved in materials in thin film form.…”
Section: Mismatch and Strainmentioning
confidence: 99%
“…In past years it has been revealed that ferroelectric polarization is not exclusive to polar materials and can be induced throughout the nonferroelectric layer of the heterostructure by combining a nonferroelectric oxide such as SrTiO 3 with a ferroelectric oxide, e.g., BaTiO 3 [7], or even with another nonferroelectric oxide, e.g., LaCrO 3 [8]. Moreover, the emergence of net ferroelectric polarization was recently demonstrated for nanometer-thick films of SrTiO 3 [9] where this effect was attributed to electrically induced alignment of polar nanoregions that can naturally form because of the presence of intrinsic defects in SrTiO 3 crystals.…”
Section: Introductionmentioning
confidence: 99%